Avaliação do envolvimento de células tronco autólogas de medula óssea em associação com técnica de tubulização por prótese de silicone na regeneração do nervo tibial de coelhos - Colomé, Lucas Marques (2007)
This study presents an experimental model of an acute defect in a peripheral nerve to evaluate neural regeneration using a tubulization technique associated with the inoculation of autologous stem cells from bone marrow. A total of 12 New Zealand white rabbits underwent a bilateral dissection of the tibial nerve followed by repair with silicone tubulization. On the left tibial nerve of all animals, the tube was filled with autologous bone marrow-derived stem cells collected from the humerus. For control, using the same repair technique, tubes were filled with a NaCl solution in the right tibial nerve. After 30 days of observation, the animals were euthanized and a histological evaluation of the collected nerve segments was performed by staining with hematoxylin-eosin, luxol fast blue, and toluidine blue. From the results it is possible to conclude that the transplanted autologous stem cells associated with the tubulization technique present an advantage in the peripheral nerve regeneration process